Glycoprotein M6B Interacts with TβRI to Activate TGF‐β‐Smad2/3 Signaling and Promote Smooth Muscle Cell Differentiation. (27th November 2018) - Zhang, Xiaomeng; Xie, Huaning; Chang, Pan; Zhao, Huishou; Xia, Yunlong; Zhang, Ling; Guo, Xiong; Huang, Chong; Yan, Feng; Hu, Lang; Lin, Chen; Li, Yueyang; et al.
Abstract: Smooth muscle cells (SMCs), which form the walls of blood vessels, play an important role in vascular development and the pathogenic process of vascular remodeling. However, the molecular mechanisms governing SMC differentiation remain poorly understood. Glycoprotein M6B (GPM6B) is a four‐transmembrane protein that belongs to the proteolipid protein family and is widely expressed in neurons, oligodendrocytes, and astrocytes. Previous studies have revealed that GPM6B plays a role in neuronal differentiation, myelination, and osteoblast differentiation. In the present study, we found that the GPM6B gene and protein expression levels were significantly upregulated during transforming growth factor‐β1 (TGF‐β1)‐induced SMC differentiation. The knockdown of GPM6B resulted in the downregulation of SMC‐specific marker expression and repressed the activation of Smad2/3 signaling. Moreover, GPM6B regulates SMC Differentiation by Controlling TGF‐β‐Smad2/3 Signaling. Furthermore, we demonstrated that similar to p‐Smad2/3, GPM6B was profoundly expressed and coexpressed with SMC differentiation markers in embryonic SMCs. Moreover, GPM6B can regulate the tightness between TβRI, TβRII, or Smad2/3 by directly binding to TβRI to activate Smad2/3 signaling during SMC differentiation, and activation of TGF‐β‐Smad2/3 signaling also facilitate the expression of GPM6B. Taken together, these findings demonstrate that GPM6B plays a crucial role in SMC differentiation and regulates SMC differentiation through the activation of TGF‐β‐Smad2/3 signaling via direct interactions with TβRI. This finding indicates that GPM6B is a potential target for deriving SMCs from stem cells in cardiovascular regenerative medicine.Stem Cells 2018 Stem Cells 2019;37:190–201 Abstract : In summary, the present study revealed that GPM6B play a crucial role in SMC differentiation. GPM6B promotes SMC differentiation through the activation of TGF‐β‐Smad2/3 signaling via regulating the tightness between TβRI and TβRII or Smad2/3 by directly binding to TβRI to activate Smad2/3 signaling, and activation of TGF‐β‐Smad2/3 signaling also facilitate the expression of GPM6B.